Meteorological-tower induced wind-field perturbations - Hsi, George, author; Cermak, J. E. (Jack E.), author; Fluid Mechanics Program, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1965)
The objective of this study was to determine how the presence of a typical meteorological tower disturbs the local wind pattern . This study provides data which can be used to correct wind speeds measured by anemometers in the field. Experimental results in this paper are based on data taken upstream of , around, and downstream from a 1:4 scale model of a 20 ft segment of the prototype tower.
CER65GH-JEC49.
October 1965.
U.S. Army Material Command Washington 25, D.C.
Keywords: Meteorological stations; Winds